Maturation of Female Yellow Rasbora (Rasbora Lateristriata Bleeker, 1854) Using Oodev at Different Doses in Feed - Rey, Juniman; Widiyanto, Slamet; Retnoaji, Bambang (Universitas Gadjah Mada, 2023)
The current high demand for Yellow rasbora (Rasbora lateristriata) is not supported by the availability of captured Yellow rasbora in nature. Aquaculture is the most rational way of utilizing biological natural resources. In intensive aquaculture, it is necessary to optimize all processes that occur in aquaculture, including hatchery. However, the common problem that often happens in hatchery activities is spawning which depends on the season. The hormonal manipulation technique is an appropriate way to stimulate gonadal maturation. Oodev is a hormonal combination of pregnant mare serum gonadotropin and anti-dopamine to stimulate gonadal maturation. The purpose of this study was to determine the effectiveness of using the Oodev with different doses in feed to accelerate gonad maturation of female Yellow rasbora. The study was carried out with four treatments and three replications in 21 days with different doses of Oodev, such as; A (Feed without Oodev), B (0.5 mL/kg feed), C (1 mL/kg feed) and D (2 mL/kg feed). The parameters observed in this study were gonad maturity level, histological structure of ovary, gonadosomatic index, fecundity, and diameter of eggs. The results showed that the dose of Oodev at 1.0 mL/kg feed was an effective dose to optimize the gonad maturity of female Yellow rasbora. This is proven by the highest results shown on all parameters, such as; the maturity level in the IV phase, histological structure of the ovary which showed the dominance of the oocyte maturation phase, gonadosomatic index of 14.014%, the fecundity of 721 eggs, and egg diameter of 0.865 mm. In conclusion, using Oodev in feed at a dose of 1.0 ml/kg of feed for 21 days is an effective dose to optimize the maturation of female Yellow rasbora.